Development of bovine abomasum in prenatal period - Nascimento, Gabriela Mansano do [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Perri, Sílvia Helena Venturoli [UNESP]; Monteiro, Cristina Maria Rodrigues [UNESP] (My University, 2013)
For this purpose, samples of Nelore fetus abomasum (Bos taurus indicus) were classified into five groups: 1 – fetuses with 9 to 15 weeks (8 to 21 cm) of gestation, 2 – fetuses with 16 to 22 weeks (23 to 37 cm), 3 – fetuses at 23 to 29 weeks (40 to 58 cm) 4 – fetuses with 30 to 36 weeks (61 to 77 cm) and 5 – fetuses with 37 to 43 weeks (79 to 88 cm). Histologic sections were stained with Hematoxylin and eosin, picrosirius and Mallory’s trichrome methods and examined under light microscopy. In fetus with 11 cm of length showed deep mucosa, wide folds and villi lined by single cylindrical epithelium, lamina propria, submucosa, muscular sublayers and serosa. Fetus with 13.5 cm, villi were evident and muscular layer of the mucosa was formed. At 16.5 cm, could be seen an increase in mucosa glands size and number. In fetus of 26 cm, showed gastric mucous glands at great number and ramifications. At 29 cm large folds, were observed. At 37 cm, showed glandular epithelium, muscular layer of the mucosa and muscular layer well development. Fetus with 42 cm, showed deep glands with corresponding mucous cells surrounding by thin lamina propria. It was concluded that the histomorphometric values of muscular layer and total abomasum wall were increased for all groups except for groups 4 and 5 which there was a decline of values, without presenting a significant difference and there was no continuous pattern of growth for other components of abomasum wall.

Para esta pesquisa, amostras de abomaso de fetos da raça Nelore (Bos taurus indicus) foram divididos em cinco grupos: 1o – fetos com 9 a 15 semanas (8 a 21cm) de gestação, 2o – fetos com 16 a 22 semanas (23 a 37 cm), 3o – fetos com 23 a 29 semanas (40 a 58 cm), 4o – fetos com 30 a 36 semanas (61 a 77 cm) e 5o – fetos com 37 a 43 semanas (79 a 88 cm). Os cortes histológicos foram corados com Hematoxilina e Eosina, picrossirius e Tricrômico de Mallory e examinados ao microscópio de luz. No feto de 11 cm, observaram-se pregas mucosas largas, vilosidades revestidas por epitélio simples cilíndrico, lâmina própria, tela submucosa, túnica muscular com estratos interno e externo e serosa. Aos 13,5 cm, as vilosidades eram evidentes com formação da lâmina muscular da mucosa. Aos 16,5 cm, houve aumento em número e tamanho das glândulas mucosas. No feto de 26 cm, observou-se aumento das túnicas e ramificações das glândulas. Aos 29 cm, observou-se aumento no tamanho das pregas. Com 37 cm, houve aumento do epitélio glandular, lâmina muscular da mucosa e túnica muscular. Com 42 cm, as glândulas eram profundas com células mucosas e lâmina pró- pria delgada. Concluiu-se que as os valores histomorfométricos da túnica muscular e parede total do abomaso foram crescentes para todos os grupos, com exceção dos grupos 4 e 5 para os quais houve queda dos valores, sem diferença significante e não houve crescimento contínuo para os demais constituintes da parede do abomaso.
Desenvolvimento do abomaso de bovinos no período pré-natal
Keywords: Morphology; Abomasum; Fetuses; Ruminants; Morfologia; Abomaso; Fetos; Ruminantes